The Routledge Handbook Of Parliamentary Administrations - Christiansen, Thomas; GRIGLIO, Elena; Lupo, Nicola (Taylor & Francis, 2023)
The Routledge Handbook of Parliamentary Administrations brings together an international, multidisciplinary group of contributors providing a systematic and comprehensive analysis of parliamentary administrations. Including chapters on the administrations of national parliaments in every member state of the European Union, in most of the EU candidate countries and in key liberal democracies around the world, this book represents a uniquely broad-ranging resource. Each national system is treated in a consistent manner, with authors providing relevant facts, ﬁgures and critical analysis according to a common framework. Additionally, it provides coverage of transnational parliamentary administrations in diﬀerent regions around the globe and includes a number of cross-cutting chapters, addressing key issues of relevance for a better understanding of parliamentary administrations such as the potential for politicisation, professionalisation, digitalisation or Europeanisation with the comparative analysis of diﬀerent national experiences. This handbook will enable readers to better comprehend the role and inﬂuence of parliamentary administrations and in doing so will enhance our understanding of their importance for the eﬀective functioning of representative democracy more generally. The Routledge Handbook of Parliamentary Administrations constitutes a unique tool and prime reference for any researcher, scholar or practitioner working in the area of parliamentary and legislative studies, governance, democracy, public policy and administration, as well as more widely to European studies, general political science and comparative politics.